Inter-departmental correspondence : extract of letter from Alexander Bain, Epsom Divisional Labour Party - Epsom Divisional Labour Party
038-0032-001 Inter-Departmental THE LABOUR PARTY This form is for use when letters include subjects for attention by more than one Department From (Organisation) Epsom D.L.P. Name of Sender Alexander Bain, Address 13, The Avenue, Worcester Park. Date of Letter 17.11.41 Subject (ONE SUBJECT ONLY) EXTRACT We have a number of Basque children who have been living in a home in Banstead for some years. Our Party in common with T.U. branches and other bodies contributed to their support for a long time quite regularly. Recently owing to our falling membership (one third of what it was) we have given little or nothing - but still they send appeals. What we feel is, now that the international situation has changed and we are fighting the ideological war that Eden wanted to avoid, perhaps the Government would help them. Many of these children have gone into industry and the remainder will soon be ready to follow - so that the Government's obligation would not be a very serious one. Perhaps the N.E.C. would examine this proposal and press it in the proper quarter. [ ] Carshalton 20 Extracted by Secretary, Dept. To International Dept. for Sub Committee Date L233156 292/946/38/32